Critical Events and Attitude Change: Support for Gun Control After Mass Shootings. Issue 4 (23rd May 2018) - Rogowski, Jon C.; Tucker, Patrick D.
Abstract : When and to what extent do crises and significant events induce changes in political attitudes? Theories of public opinion and policymaking predict that major events restructure public opinion and pry open new political opportunities. We examine the effect of major events on support for public policies in the context of the Sandy Hook Elementary School mass shooting in December 2012 using a nationally representative panel survey of US adults. Across both cross-sectional and within-subject analyses, we find no evidence that Americans granted greater support for gun control after the Sandy Hook shooting. Our null findings persist across a range of political and demographic groups. We also find no evidence of attitude polarization as a result of Sandy Hook. Our results suggest that elite polarization in a particular issue area leads citizens to employ motivated reasoning when interpreting critical events, thereby reducing the capacity for attitude change. Our findings have important implications for identifying the conditions under which major events affect support for public policies and create political opportunities for policy change.